Initial Use of 100% but Not 60% or 30% Oxygen Achieved a Target Heart Rate of 100 bpm and Preductal Saturations of 80% Faster in a Bradycardic Preterm Model - Mausma Bawa; Sylvia Gugino; Justin Helman; Lori Nielsen; Nicole Bradley; Srinivasan Mani; Arun Prasath; Clariss Blanco; Andreina Mari; Jayasree Nair; Munmun Rawat; Satyan Lakshminrusimha; et al. (Children, 2022)
Background: Currently, 21–30% supplemental oxygen is recommended during resuscitation of preterm neonates. Recent studies have shown that 58% of infants < 32 week gestation age are born with a heart rate (HR) < 100 bpm. Prolonged bradycardia with the inability to achieve a preductal saturation (SpO2) of 80% by 5 min is associated with mortality and morbidity in preterm infants. The optimal oxygen concentration that enables the achievement of a HR ≥ 100 bpm and SpO2 of ≥80% by 5 min in preterm lambs is not known. Methods: Preterm ovine model (125–127 d, gestation equivalent to human neonates < 28 weeks) was instrumented, and asphyxia was induced by umbilical cord occlusion until bradycardia. Ventilation was initiated with 30% (OX30), 60% (OX60), and 100% (OX100) for the first 2 min and titrated proportionately to the difference from the recommended preductal SpO2. Our primary outcome was the incidence of the composite of HR ≥ 100 bpm and SpO2 ≥ 80%, by 5 min. Secondary outcomes were to evaluate the time taken to achieve the primary outcome, gas exchange, pulmonary/systemic hemodynamics, and the oxidative injury. Results: Eighteen lambs (OX30-6, OX60-5. OX100-7) had an average HR < 91 bpm with a pH of <6.92 before resuscitation. Sixty seven percent achieved the primary outcome in OX100, 40% in OX60, and none in OX30. The time taken to achieve the primary outcome was significantly shorter with OX100 (6 ± 2 min) than with OX30 (10 ± 3 min) (* p = 0.04). The preductal SpO2 was highest with OX100, while the peak pulmonary blood flow was lowest with OX30, with no difference in O2 delivery to the brain or oxidative injury by 10 min. Conclusions: The use of 30%, 60%, and 100% supplemental O2 in a bradycardic preterm ovine model did not demonstrate a significant difference in the composite primary outcome. The current recommendation to use 30% oxygen did not achieve a preductal SpO2 of 80% by 5 min in any preterm lambs. Clinical studies to optimize supplemental O2 in depressed preterm neonates not requiring chest compressions are warranted.